2011
DOI: 10.1186/2192-0567-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a pellet boiler with Stirling engine for m-CHP domestic application

Abstract: A new sustainable technology has been designed by Fondazione Bruno Kessler through its unit Renewable Energies and Environmental Technologies. This technology is realized integrating in a single system (1) a Stirling engine (mRT-1K) from a pre-engineering design of Allan J. Organ; (2) a micro-heat exchanger technology, to reduce the net transfer unit deficit on the hot side of the heat engine; (3) a customized pellet boiler, able to extract electrical and thermal power; and (4) a customized hydraulic circuit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Stirling engine heads adapted to receive heat from solid fuel systems are intensively developed by means of advanced numerical analyses. The example of the concept Stirling engine with an additional heat exchanger located at an angle of 45 • , designed specifically for the system analyzed by the authors [79,80] is shown in Figure 11. The manufactured engine based on this design is shown in Figure 12.…”
Section: Stirling Engine Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stirling engine heads adapted to receive heat from solid fuel systems are intensively developed by means of advanced numerical analyses. The example of the concept Stirling engine with an additional heat exchanger located at an angle of 45 • , designed specifically for the system analyzed by the authors [79,80] is shown in Figure 11. The manufactured engine based on this design is shown in Figure 12.…”
Section: Stirling Engine Applicationsmentioning
confidence: 99%
“…Figure13. Side view of a heat exchanger adapted to operate with a Stirling engine and a solid fuel system[80].…”
mentioning
confidence: 99%
“…Among these contributions we find the system infinea [52] or solar dish [53]. Other precommercial prototypes (see Relevant Websites section) have been developed in the field of cogeneration of electricity and heat (CHP), the cogeneration units Cleanenergy [51], Whispergen [54], Stirling DK, and the "Sunmachine" gas or biomass [55]. All solutions are based on high-temperature sources.…”
Section: Electricity Production From Solar Energymentioning
confidence: 99%
“…Figure 1). The literature mentions several solid biomass-fuelled micro-CHP systems associated to various cogeneration devices: a Stirling hot air engine [1][2][3][4], an Organic Rankine Cycle (ORC) turbine [5] and a thermoelectric generator [6]. Although no study has dealt with the performances of a solid biomass-fuelled micro-CHP system with an Ericsson hot air engine yet, this cogeneration device is well adapted in such facilities [7].…”
Section: Introductionmentioning
confidence: 99%
“…To determine the working conditions and the performances of the solid biomass-fuelled micro-CHP systems and of their components, an energetic analysis is mostly applied [1,2,5,6]. Such studies may be completed with exergetic analyses, following the example presented by [14] with a natural gas micro-CHP system, in order to highlight the zones of exergy destruction and allow an improved optimization of the working conditions to enhance the performances.…”
Section: Introductionmentioning
confidence: 99%